2013
DOI: 10.1097/aln.0b013e31829bd770
|View full text |Cite
|
Sign up to set email alerts
|

Individually Optimized Hemodynamic Therapy Reduces Complications and Length of Stay in the Intensive Care Unit

Abstract: Early goal-directed hemodynamic therapy based on cardiac index, stroke volume variation, and optimized global end-diastolic volume index reduces complications and length of ICU stay after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 49 publications
6
70
0
2
Order By: Relevance
“…Current perioperative ‘goal-directed therapy’ studies have been focused mainly on systemic haemodynamic parameters [11,39] and may contribute to improvements in survival after major surgery by using perioperative plasma volume expansion [12,39] or a more restricted fluid approach [40]. Moreover, there is to date no uniform goal-directed strategy aimed at resuscitation of regional peripheral blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current perioperative ‘goal-directed therapy’ studies have been focused mainly on systemic haemodynamic parameters [11,39] and may contribute to improvements in survival after major surgery by using perioperative plasma volume expansion [12,39] or a more restricted fluid approach [40]. Moreover, there is to date no uniform goal-directed strategy aimed at resuscitation of regional peripheral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the success of early, goal-directed haemodynamic therapy has demonstrated the importance of maintaining and improving tissue oxygenation and has shown that early detection and correction of altered tissue perfusion reduce postoperative complications [2,11]. Accordingly, their importance is also the basis for stressing the need to monitor postoperative early warning signals for occult tissue hypoperfusion [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have clearly demonstrated the beneficial effects of this approach in cardiac surgery. [10][11][12][13][14][15] However, the changes in ScvO 2, ∆Pv-aCO 2 and lactate reflect different pathophysiological processes and events. Therefore, adequate evaluation of each parameter and their relationship could be helpful to manage intensive care.…”
Section: Introductionmentioning
confidence: 96%
“…Considering the large variability of biometric parameters such as body weight (BW) and height volumetric parameters are usually adjusted for these biometric variables to improve inter-individual comparisons and to allow for homogenous normal ranges. GEDV indexed to body surface area (BSA) is termed GEDVI and has been demonstrated to be useful in assessing preload and to guide fluid therapy in several studies [1][2][3][4][5][6][7]. Nevertheless, some studies using algorithms based on GEDVI have failed to improve outcome [8,9].…”
Section: Introductionmentioning
confidence: 98%